Treatment of Domestic Wastewater with Combination of Phytoremediation and Filtration Using Activated Carbon of Tea Dregs - Nisa Nurhidayanti; Dodit Ardiatma; Jamaludin Tasdik (Universitas Diponegoro, 2021)
One source of water pollution comes from domestic wastewater as a result of daily human activities. As one of the work units in the field of education, the university also produces domestic liquid waste that needs to be processed so as not to pollute the environment. The use of the phytoremediation method with water jasmine and water hyacinth combined with the use of tea dregss as an activated carbon filter is one method that can be used to treat domestic greywater wastewater. The purpose of this study was to determine the efficiency of reducing levels of COD, BOD, TSS, NH3, and turbidity in domestic greywater waste at Pelita Bangsa University by phytoremediation methods using water jasmine plants and water hyacinth plants with a combination of filters from tea dregss. The research procedure starts by making activated carbon from tea dregss, characterizing activated carbon with SEM, sampling greywater wastewater, characterizing wastewater test, plant acclimatization, range-finding test, phytoreactor test with activated carbon filter, and data analysis. The phytoremediation method with a combination of filtration using tea dregss activated carbon produces an efficiency of 99.61% COD reduction, 100% BOD, 98.68% TSS, 100% ammonia, and 97.50% turbidity.